Comparison of contraction rates of epigastric and extended dorsal island skin flaps in rats - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2019)
Flap surgery is a wide field in plastic and reconstructive surgery practice and experimental research is needed to improve surgical success. These research is often performed on rats. Rat is a loose-skinned animal and contraction of skin flaps on rats is an underestimated condition. Besides this variable contraction of survived and necrotic tissues may mislead calculations and results. In this study, contraction patterns of epigastric and dorsal island skin flaps were investigated to identify this phenomenon. Forty-two male Sprague-Dawley rats were divided into four groups. Eleven epigastric flaps with unilateral pedicles, 11 epigastric flaps with bilateral pedicles, 10 extended dorsal island skin flaps with unilateral pedicles, and 10 extended dorsal island skin flaps with bilateral pedicles were prepared. Total, necrotic and viable flap areas were calculated from standardized photographs which were taken daily. The animals were placed on marked papers and image processing software was used the calculate flap areas from the photographs. Respect to these daily flap areas, the contraction rates in epigastric flaps were highly significant. The area loss in necrotic tissues were faster than the viable areas. Compared to the epigastric flaps, the contraction was not significant in extended dorsal island skin flaps flap groups. In conclusion, the rat extended dorsal island skin flap is a more reliable model for experimental flap research, which is resistant to contraction, when compared to the epigastric skin flap model.
Keywords: Flap contraction; rat; experimental flap surgery; WOUND CONTRACTION; CUSTOM-MADE; VEST; AUTOCANNIBALIZATION; SURVIVAL